Microstrip Patch Antenna Design in Circular Topology for Ultra High-Frequency 900MHz Radio Spectrum: Size Reduction Technique and Defected Ground Structure Effects - Hamid S.H.; Hock G.C.; Kiong T.S.; Ferdous N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antenna grounds; Computer software; Defected ground structures; Defects; Directional patterns (antenna); Electric network analyzers; Energy harvesting; Omnidirectional antennas; Rectennas; Size determination; Slot antennas; Topology; Antenna performance; Defected ground plane; Micro-strip patch antennas; Operating frequency; Simulations and measurements; Size reduction techniques; Ultra-high frequency; Vector network analyzers; Microstrip antennas